Consumer Preference for Locally Grown Produce: An Analysis of Willingness-To-Pay and Geographic Scale - Perry Burnett; Todd H. Kuethe; Curtis Price (Journal of Agriculture, Food Systems, and Community Development, 2016)
This study examines consumers' willingness-to-pay for locally grown fresh produce under five definitions of "local," including a generic term "locally grown" and four geographic intervals: multistate, state, regional, and county. A survey of 482 area residents in Evansville, Indiana, was conducted to examine how estimated price premiums vary with geographic scale. The results suggest that as the geographical scale shrinks, the estimated price premium increases. However, the differences across geographic intervals may not be substantial. Therefore, producers may expect similar price premiums when sourcing from larger geographic areas, and local food systems may ensure consistent profit margins while minimizing the costs of acquiring "local" foods.